Fermentative hydrogen production from microalgal biomass by a single strain of bacterium Enterobacter aerogenes – Effect of operational conditions and fermentation kinetics. (April 2018) - Batista, Ana Paula; Gouveia, Luísa; Marques, Paula A.S.S.
Abstract: Biohydrogen production through dark fermentation is a promising technology for generating renewable energy, while using microalgal biomass as a third generation feedstock can further increase the sustainability of the process. In the present study, Scenedesmus obliquus was used as model microalga substrate for studying the impact of operational parameters in batch dark fermentation trials using a strain of Enterobacter aerogenes bacteria. (i) The initial gas-liquid ratio in the bioreactor (from 1.3 to 8.2) was tested, resulting in higher bioH2 yields for ratios above 5. (ii) Different bacterial growth, inoculation procedures and fermentation media were tested in combined experiments. The best conditions were chosen by maximising bioH2 yield and minimising production time and costs. (iii) The autoclave sterilization effect on sugar extraction and bioH2 yield was tested for different microalga concentrations (2.5–50 g/L) with best results attained for 2.5 g/L (81.2% extraction yield, 40.9 mL H2 /g alga). For the best operational conditions, fermentation kinetics were monitored and adjusted to the Modified Gompertz model, with t 95 (time required for bioH2 production to attain 95% of the maximum yield) below 4.5 h. The maximum hydrogen production was higher when using wet algal biomass enabling the energy consuming biomass drying step to be skipped. Highlights: Scenedesmus obliquus was used as feedstock for bioH2 production by Enterobacter aerogenes . Initial gas-liquid ratios above 5 in the bioreactor provide higher bioH2 yields. Pre-inoculum and inoculation procedures significantly affect bioH2 yields. Autoclave sterilization can have effect on the sugar extraction from S. obliquus biomass. BioH2 production kinetics revealed that stationary phase can be achieved under 4.5 h.